2021
DOI: 10.1177/13567667211066544
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Applications for Travel Booking: Impacts of Application Quality and Brand Trust

Abstract: The increasing use of mobile applications by travellers and the high adaption of tourism companies into this new contact and sales platform, made it necessary to comprehensively investigate the mobile application users’ behaviours. This research combines the Stimulus-Organism-Response (S-O-R) framework and Technology Acceptance Model (TAM) to develop a theoretical background in examining travel booking behaviour of mobile application users. The conceptual model suggests that mobile application quality (MAQ) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 100 publications
4
14
0
Order By: Relevance
“…Based on the results of estimating structural parameters using SEM, hypothesis 1 is supported. The results of this study are consistent with studies conducted by Holden and Karsh (2010), Blut, Wang, and Schoefer (2016), Venkatesh, Thong, and Xu, (2012), Chauhan (2015), and Albayrak et al (2021) which indicate the significant strength of perceived usefulness in explaining and predicting intentions to use or adopt new technological systems. In the TAM framework, PU is hypothesized as a direct predictor of behavioral intention to use the technology of interest (Park et al, 2014;Catchpole et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Based on the results of estimating structural parameters using SEM, hypothesis 1 is supported. The results of this study are consistent with studies conducted by Holden and Karsh (2010), Blut, Wang, and Schoefer (2016), Venkatesh, Thong, and Xu, (2012), Chauhan (2015), and Albayrak et al (2021) which indicate the significant strength of perceived usefulness in explaining and predicting intentions to use or adopt new technological systems. In the TAM framework, PU is hypothesized as a direct predictor of behavioral intention to use the technology of interest (Park et al, 2014;Catchpole et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…In the TAM framework, PU is hypothesized as a direct predictor of behavioral intention to use the technology of interest (Park et al, 2014;Catchpole et al, 2022). Previous studies have shown that PU is positively related to sustained intention in the context of research on the use or adoption of new technology systems, such as e-text (Baker-Eveleth & Stone, 2015;Stone & Baker-Eveleth, 2013), instant messaging (Wang, Ngai, & Wei, 2011), mobile service providers (Abbas & Hamdy, 2015;Catchpole et al, 2022), online travel services (Li & Liu, 2014;Albayrak et al, 2021), e-learning (Lin & Wang, 2012), blog learning (Tang, Tang, and Chiang, 2012), as well as knowledge creation (Chou et al, 2009). This study further emphasizes that when elementary teachers believe in the benefits of online learning technology during ELT, the intention to use this technology in the ERL process will be higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When making an offline purchase, reliable information comes from personal sensory examination, whereas online shopping is influenced by the customer's purchase intention in addition to social influence or knowledge and curiosity [84]. To overcome the barrier of not being able to view products before purchasing them [85], good trust in shopping requires high quality online services [86,87] and professional online platforms [88]. Improved trust when shopping online occurs when full information about product attributes is available, and for this reason, care should be taken with this aspect of online sales.…”
Section: Discussionmentioning
confidence: 99%
“…They may access their frequently answered questions (FAQs) on issues relating to ancillary services like insurance products and loyalty points. At times, they use their live chat facilities that are usually operated via artificially intelligent (AI) chatbot technologies (Adam et al, 2020;Camilleri, 2019), through social networking services (SNSs), including Facebook Messenger or WhatsApp, among others (Albayrak et al, 2021;Buhalis and Moldavska, 2022;Camilleri and Troise, 2022;Lee et al, 2020;McLean and Osei-Frimpong, 2019), to resolve their queries or complaints. Camilleri and Kozak (2022a) sought to explore the antecedents affecting intentions to use travel websites.…”
Section: Interactive Travel Appsmentioning
confidence: 99%